Resosialisasi Panduan Pelayanan Unit Paliatif Kardiovaskular - Diki Armansyah Damanik; Hanny Handiyani; La Ode Abdul Rahman; Hana Mutiasari; Tini Sumiarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to conduct resocialization by providing repeated understanding and service guidelines as a reference in services that staff can follow and implement. The method used is a pilot study using observation techniques, interviews, and questionnaires with the head of the room managerial function approach. The study results showed that the resocialization of cardiovascular palliative service guidelines with audio-visual methods in the form of videos made staff more familiar with and understanding cardiovascular palliative care. Resocializing service guidelines in cardiovascular palliative unit services show increased staff knowledge about cardiovascular palliative services. In conclusion, resocialization can increase knowledge and understanding of regulation. Keywords: Cardiovascular Palliative Guide, Kurt Lewin Changes, Resocialization